Ecological situation of acacia tortilis subspecies raddiana. Case study: In white nile state, Sudan - Goda MMB; Dosougi MA; Osman A; A Musa Ibrahim (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2021)
This study conducted during the season 2017 at ED-Duem Locality which is laid at Northern White Nile State of Sudan, the main objectives of this study was measurement, listing of all acacia raddiana tree sites their assessed the physical characteristics of the height, diameter at breast height and were account the abundance, dominance, and survival % of natural regeneration of acacia raddiana tree as the main species. The researcher used the systematic circular sampling plots methodology which established with total number of 130 sample plots. The sample plots were circular in shape with a radius of 17.84 m (0.1 ha in area.). In these sample plots all trees with diameter at breast height (dbh) equal to or greater than seven centimeters were measured for tree species, and the regeneration survey in each sample plot (10) quadrats ( subplots) of 1mx1m (1m²), the regeneration survey in each sample plot (10) quadrats ( subplots) of 1mx1m (1m²) were calculated. The results showed no significant different for acacia raddiana tree in eight sites, and the survival rate of Acacia raddiana regeneration are (20.4 -23.9%).